RESPON BIBIT KELAPA SAWIT ATAS PEMBERIAN PUPUK ORGANIK PADA TANAH GAMBUT DI KALIMANTAN TENGAH (Palm oil seedling response of organic fertilizer on peat soil in Central Kalimantan): Sustiyah1*); Sulistiyanto, Y. 1); Damanik, Z. 1) - Admin journal (Fakultas Pertanian Universitas Palangka Raya, 2018)
ABSTRACTThe purpose of this study was to determine response of main nursery palm seedlings forapplication of organic fertilizers on soil peat. The experiment used completely randomized factorialdesign consisting of two factors. The first factor was petroganik fertilizers (P) consists of fourlevels: Po = control or no petroganik (0 kg/plants), P1 = petroganik 0,5 kg/plants, P2 = Petrogenik1 kg/plants; P3 = Petrogenik 2 kg/plans. The second factor was bokhasi kayambang fertilizers (K)consists of four levels: Ko = control or no bokhasi kayambang (0 kg/plants); K1 = BokhasiKayambang 0,5 kg/plants; K2 = Bokhasi Kayambang 1 kg/plants; K3 = Bokhasi Kayambang 2kg/plants. The each treatment was replicated five times. Observed variables were plant height,number of leaf midrib, number of primary root and length of primary root. Results showed thatinteraction between the application of petroganik fertilizers 2 kg/plants and bokhasi kayambangfertilizers 1 kg/plants (P3K2), respond positively to the growth of oil palm seedlings main nurserywhith soil pH 5,95. This treatment produced the highest plant height, the largest number of leafmidrib, the best root number and length of primary root.Key word : oil palm seedling, rubber waste liquid, fertilizer